Pin Up Style dalam Fotografi Fashion Kontemporer - Tiara Sekar Adhitia; M. Kholid Arif Rozaq; M. Fajar Apriyanto (Institut Seni Indonesia Yogyakarta, 2019)
Fashion becomes a social symbol that gives the cultural identity to a person. Pin up style has existed since the late 1950s. This style which is a combination of urban style and pop culture is identical with a light, tight, and semi-open dress. The image sticking on pin up style fashion makes the women called as